Recent developments on injectable calcium phosphate bone cement - Hablee, Sufiamie; Razali, Nurul Nadirah; Alqap, Asep Sofwan Faturohman; Sopyan, Iis (Bentham Science Publishers B.V., 2016)
New emerging micro-invasive bone grafting techniques have recently risen the interest towards injectable calcium phosphate cement (CPC) as bone filling material that is able to set itself within the body temperature. There are various formulations of injectable CPC that have been developed in recent years. The development of injectable CPC mainly focuses on getting optimum setting times, mechanical properties, injection capabilities and in vivo properties so that the cement is clinically applicable for orthopedic, dental, craniofacial and maxillofacial, vertebroplasty and kyphoplasty, and drug delivery applications. The existing studies on injectable CPCs have investigated the effects of some factors, such as liquid to powder (P/L) ratio, types solid and liquid phase used, concentration of the liquid phase, density and porosity of the cement, particle size of the cement powder and its crystallinity, needle size, and use of setting retardants, setting accelerators and cohesion promoters on the handling, mechanical and biological properties of the cement. The aim of this paper is to review the recent developments of injectable CPC for bone filling materials. Some prominent patents related to the developments of injectable CPC are also reviewed